2020
DOI: 10.3892/ol.2020.11361
|View full text |Cite
|
Sign up to set email alerts
|

miR‑939‑3p promotes epithelial‑mesenchymal transition and may be used as a prognostic marker in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of cancer worldwide with a high morbidity and mortality rate. An increasing number of studies have demonstrated that microRNAs (miRNAs) serve an important role in HCC. The present study investigated the role of miR-939-3p in HCC. It was demonstrated that miR-939-3p was upregulated in HCC cell lines and HCC tissues compared with normal liver cell lines and paired normal tissues, respectively. It was also found that upregulation of miR-939-3p express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…MEG3 can bind a few miRNAs at the sites that undergo editing (among them, miR-939-39 and miR-331-3p). Interestingly, miR-331-3p can inhibit glioma progression [ 43 ], while miR-939-3p can promotes hepatocellular carcinoma and lung cancer [ 44 , 45 ]. We believe that editing loss in lncRNA in GBM can play an important role in either releasing miRNAs that can promote cancer (miR-939-3p) and/or binding tumor suppressor miRNAs (miR-331-3p).…”
Section: Discussionmentioning
confidence: 99%
“…MEG3 can bind a few miRNAs at the sites that undergo editing (among them, miR-939-39 and miR-331-3p). Interestingly, miR-331-3p can inhibit glioma progression [ 43 ], while miR-939-3p can promotes hepatocellular carcinoma and lung cancer [ 44 , 45 ]. We believe that editing loss in lncRNA in GBM can play an important role in either releasing miRNAs that can promote cancer (miR-939-3p) and/or binding tumor suppressor miRNAs (miR-331-3p).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that miRNAs could exert their biological function mainly by binding their target mRNAs. 30,31 In the current study, we found cyclin E1 was a direct target of miR-1231, which has been regarded as a key regulator in cell cycle. 32 In addition, CDK2 was found to be downregulated in pancreatic cancer cells in the presence of ABHD11-AS1 shRNA1.…”
Section: Discussionmentioning
confidence: 57%
“…Our findings are in agreement with those of Mazza et al, who demonstrated that hsa-miR-6126 was one of the most significantly increased miRNAs in the plasma of PDAC patients [41], and the same hsa-miR-6126 has been found in the tumor tissues of five patients with stage II colon cancer but not in cancer-free tissues [42]. hsa-miR-939-5p, of potential interest for its role in invasive cancer, is reportedly upregulated in lung adenocarcinomas [43], hepatocellular carcinomas [44,45], ovarian cancer tissue [46] and in the promotion of blood vessel invasion in breast cancer [47]. The recent study by Shen et al [48] shed some light on the role of this hsa-miR-939-5p in PDAC biology and prognosis.…”
Section: Discussionmentioning
confidence: 96%